The Role of Stakeholders in The Management of Sustainable Environmental Cleanliness in Makassar City - Andi Agustang; Hairuddin K Hairuddin K; Andi Dody May Putra Agustang; Dian Meiliani Yulis (Universitas of Muhammadiyah Makassar, 2023)
The purpose of this research was to examine the role of universities, business entities/private parties, urban village officers/pamong and non-governmental organizations as stakeholders in the management of sustainable environmental hygiene in the city of Makassar. Data collection was carried out using questionnaires through interviews and FGDs. Apart from that, documentation materials such as: program documents and reports on activities that have been carried out by each stakeholder are also used. Based on the results of the research, the stakeholders stated that there were 4 (four) categories of important roles and functions of environmental cleaning organizations in Makassar City, namely: (1) as a control function for urban environmental hygiene institutions, (2) these institutions are responsible for cleanliness of the Makassar city environment, (3) so that municipal solid waste can be managed efficiently and effectively, and (4) the existence of an environmental cleaning organization and functioning properly will be able to manage urban environmental cleanliness in a sustainable manner. The roles of universities, the private sector, government officials and NGOs as stakeholders in supporting local governments towards community empowerment show a tendency towards a low category. Based on the Fisher contingency test results, it can be concluded that there is a significant role for stakeholders in community empowerment in sustainable environmental hygiene management, especially urban waste.